Doradztwo rolnicze w Polsce w latach 1989-2002 - Wiatrak, Andrzej (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
In the article, author made an assessment of changes in the system of agricultural extension in Poland during the transformation period. He analysed the stages of changes in agricultural extension in Poland. Additionally, he identified the strengths and weakness of these changes. The following stages of agricultural extension development in Poland were distinguished: * stage of arrangements (1989-1990), * stage of establishing new extension system and its stabilisation (1991-1994), * stage of maintenance of agricultural extension system and gradual expansion of its bureaucracy (1995-1998), * stage of stagnation and absence of clear concept for the extension system development (1999-2002).